2002
DOI: 10.1177/009127002762491316
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Zoledronic Acid in Cancer Patients with Bone Metastases

Abstract: The pharmacokinetics, pharmacodynamics, and safety of zoledronic acid (Zometa), a new-generation bisphosphonate, were evaluated in 36 patients with cancer and bone metastases. Zoledronic acid (by specific radioimmunoassay) and markers of bone turnover were determined in plasma and urine after three consecutive infusions (qx28 days) of 4 mg/5 min (n = 5),4 mg/l5 min (n = 7),8 mg/15 min (n = 12), or 16 mg/15 min (n = 12). Zoledronic plasma disposition was multiphasic, with half-lives of 0.2 and 1.4 hours represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
266
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(288 citation statements)
references
References 16 publications
20
266
0
2
Order By: Relevance
“…Both reports involved higher doses and more frequent administration of zoledronic acid compared with our study, and significantly higher than those used in the clinical treatment of cancer-induced bone disease (4 mg infusion; ref. 17). Although the dose of 100 μg/kg research grade zoledronic acid (disodium salt, 4.75 hydrate) we used equates to the 4-mg clinical dose, this was administered weekly as opposed to every 3 to 4 weeks in clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both reports involved higher doses and more frequent administration of zoledronic acid compared with our study, and significantly higher than those used in the clinical treatment of cancer-induced bone disease (4 mg infusion; ref. 17). Although the dose of 100 μg/kg research grade zoledronic acid (disodium salt, 4.75 hydrate) we used equates to the 4-mg clinical dose, this was administered weekly as opposed to every 3 to 4 weeks in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have clearly shown the potential for zoledronic acid to induce direct antitumor effects including inhibition of tumor cell growth, induction of apoptosis, (9)(10)(11), inhibition of adhesion and invasion (12)(13)(14), and antiangiogenic activity (15,16). However, the concentrations of bisphosphonates used in these studies range from 5 to 20 μmol/L for up to 72 hours, compared with the 2 μmol/L circulating plasma concentration detectable in breast cancer patients for 1 to 2 hours following the standard 4-mg infusion of zoledronic acid (17). Antitumor effects of bisphosphonates have also been reported in in vivo model systems that mimic tumorinduced bone disease from a variety of cancer types including breast (18,19), prostate (20), leukemia (21), and multiple myeloma (22).…”
Section: Introductionmentioning
confidence: 99%
“…Both IC 50 s of ZOL against parental and P-gp-overexpressing leukaemic cells are above 60 mM, whereas of those against osteosarcoma cells were much less. It could, therefore, be argued that in the cell lines that we used, the P <0.001 P <0.001 P<0.001 P >0.05 P >0.05 P >0.05 According to a previous study evaluating ZOL efficacy for the treatment of osteoporosis (Chen et al, 2002), peak serum concentrations were in the range of 1 -3 mM and maintained for only a few hours. As IC 50 s of ZOL for MOS and LM8 cells are 1.56 and 7.36 mM, respectively, it is likely that the effect of ZOL alone might be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…infusion of the recommended clinical dose of zoledronic acid (4 mg), the drug remains in the plasma for less than 1 hr before localizing to bone. 39 Therefore, we exposed MCF7 cells to increasing concentrations of zoledronic acid for 1 hr only, followed by washing to remove the drug and a further 72-hr incubation in fresh medium. We found that zoledronic acid still induced a concentration-dependent increase in apoptosis (maximum, 4.5% apoptosis with 100 M zoledronic acid; p ϭ 0.002 compared to control; Fig.…”
Section: Effect Of Short-term Exposure To Zoledronic Acid In Mcf7 Cellsmentioning
confidence: 99%